PENGARUH PROFITABILTAS, LIKUIDITAS, LEVERAGE, KEPEMILIKAN MANAJERIAL, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Sektor Property & Real Estate Yang Terdaftar di BEI Periode 2016-2018) - Mohamad Zulman Hakim; Dirvi surya abbas; Anggi Wahyuni Nasution (Universitas Muhammadiyah Tangerang, 2020)
Financial distress is a phase of decline in financial condition that occurred before the onset of bankruptcy. This study aims to examine the effect of proftabiliy, liquidity, leverage, managerial ownership, and institutional ownership of financial distress. This research was conducted at the companies occurs on property & real estate company in Indonesia listed on the Stock Exchange in 2016-2018. The samples used were as many as 30 observations selected using purposive sampling method. The analysis technique used is panel data regression using Eviews Program. The results of the analysis of this study indicate that the profitability ratio, likuidity are able to affects the financial distress of manufacturing company with positif direction. While the leverage ratio, managerial ownership, and institusional ownership are not able to influence the probability of financial distress.